RESOLUSI KONFLIK RASIAL NIRKEKERASAN DALAM NOVEL PLAYING THE ENEMY - Shinta Fitria Utami (Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2022)
Conflict or dissension is a social interaction’s form that arises from the society. It happens because of differences, competitive interaction, prejudice, hatred, and also revenge.There are three approaches in resolating conflict, a power based approach, a right based approach, and an interest based approach. This paper contains research on literary work, that assumed, portray the resolution of racial conflict in novel Playing the Enemy by using sosiology of literature approach. The result of this research indicates that rasial conflict, that happened, are resolved using a non-violence power approach.